Publicity of Hrant Matevosyan and Valentin Rasputin from the Point of View of the Principle of Reverse Perspective - Petrosyan, David (Bulletin of Yerevan University B: Philology, 2023)
The trends of expanding the information boundaries of the media, the activity of social networks, and their new tools require a rethinking of the content and social significance of journalism. In this context, the analysis of the creative experience of literary publicists of the previous generation is of particular importance. We have chosen the famous writers G. Matevosyan and V. Rasputin, whose works are analyzed, whose creative works are considered from the point of view of the principle of reverse perspective known in painting. The theme was investigated in two main directions: the presence of iconic functions characteristic of the principle of reverse perspective in the above mentioned authors' journalism, and the manifestations of the same principle in the relationshipbetween the author and the audience. In the works of G. Matevosyan and V. Rasputin, the principle of reverse perspective opens up new ways. Rasputin's works, the principle of reverse perspective opens up new possibilities of understanding and rethinking the material. Due to the spatial and temporal vectors and multi-directional orientation of the author's point of view, remarkable functions have been revealed in them. Both authors, as writers of a society in transition, had two different audiences: Soviet and post-Soviet. While the Soviet audience was distinguished by ideological motives, awareness of common interest, the post-Soviet audience was characterized by horizontal writer-reader relations, active dialogues in social networks, etc. In the latter case, the reverse perspective unfolds in superficial dimensions. However, both writers believe in the future of high literature reflected by the vectors of reverse perspective in the spiritual world of the reader.
Keywords: principle of reverse perspective; publicism; Hrant Matevosyan; Valentin Rasputin; Pavel Florensky; iconic functions; author and audience